Adjusting Intervention Intensity to Support Students With Autism Spectrum Disorder. (May 2022) - Ma, Zijie; Travers, Jason C.
Special education and related professionals often understand the importance of adhering to intervention procedures (i.e., fidelity), but may be less familiar with concepts of intervention intensity. In some cases, professionals may correctly apply an intervention, but with insufficient intensity. This can result in an intervention failing to produce the expected benefit, which can add to student frustration, lost resources, and teacher burnout. Students with autism spectrum disorder (ASD) often benefit from intensive intervention that contains high rates of opportunities to respond. This article provides an overview of a practical guide for adjusting intervention intensity for students with ASD through a three-step process that includes identifying when to adjust intensity along with three ways to adjust intervention intensity. Additional considerations are included for analyzing student responses for data-based decision-making.